Concept FREEDOM in poetic discourse of Arcadiy Kazka: figurative, conceptual and value components - Янченко, Юлія Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article contains a contextual and structural-semantic analysis of the concept FREEDOM in the individual-author’s discourse of the poet Arcadiy Kazka. The tokens that refer to the concept, the hyponim of the concept and its associatives are higheighted. Within the framework of the linguistic and cultural approach, the main features of the concept FREEDOM were characterized, which are inherent for the conceptual picture of the poet’s world. It was found and described methods of verbal expression of the concept in poetic texts of the representative of Executed Renaissance. In particular, at the verbal level, it was examined and investigated the binary oppositions (the hyponym names), the metaphors, the color names, the emotions, the syntactic constructions. This research allows us to characterize the discourse of the era to which the poet belonged. It’s the first attempt of a detailed analysis of the concept FREEDOM on the material by Arcadiy Kazka.